THE DEVELOPMENT OF A MOBILE APPLICATION "ART-ROOM" IN THE CONTEXT OF MODERN WEB DESIGN - Tschigrin, N.A.; Dieieva, A.V. (SWorld-Ger Conference proceedings, 2024)
Considering the interest in art in the digital era, research aimed at studying and optimizing the design of mobile applications for promoting art products becomes very important for the further development of cultural space and supporting creative initiat